2017
DOI: 10.1002/2016jd025335
|View full text |Cite
|
Sign up to set email alerts
|

Development of an improved aerosol product over the Indian subcontinent: Blending model, satellite, and ground‐based estimates

Abstract: A comprehensive assessment of the aerosol optical depth (AOD) at 550 nm from European Centre for Medium‐Range Weather Forecasts (ECMWF), Moderate Resolution Imaging Spectroradiometer (MODIS), and Multiangle Imaging Spectroradiometer (MISR) has been performed with respect to the Aerosol Robotic Network (AERONET) measurements at 35 locations over the Indian subcontinent. For all of the stations, the mean relative errors for the collocated ECMWF, MODIS, and MISR AOD are 46.15%, 41.81%, and 39.98%, respectively. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In [39], the authors found a correlation coefficient of 0.73, an average error around 46.15%, and an MBE of 0.045. It was also found that only 52.12% of CAMS MACC AOD values were within ±0.05 to ±0.15 of the Aeronet AOD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In [39], the authors found a correlation coefficient of 0.73, an average error around 46.15%, and an MBE of 0.045. It was also found that only 52.12% of CAMS MACC AOD values were within ±0.05 to ±0.15 of the Aeronet AOD.…”
Section: Discussionmentioning
confidence: 94%
“…Aeronet locations were selected on the basis of proximity to BSRN locations and available data were extracted on the basis of the time period of INSAT-3D data. The AOD data from Aeronet was available at 500 nm, which was converted to 550 nm using Ångstrom law [39,40].…”
Section: Ground Measurementsmentioning
confidence: 99%
“…This is mainly because, the underlying correlation structure and the actual variance values not only dictate the pattern in which observations get merged with the background data but also decides the weights given to each of the parent datasets during the merging 20 process. In the present study, the observation error covariance matrix (O) is considered to be diagonal implying that errors in GR AAODs from different ground-based stations are uncorrelated, which is generally true and is followed earlier also (Niu et al, 2008;Zhang et al, 2008;Singh et al, 2017). As the diagonal terms of the covariance matrix refer to variance of the corresponding data, the diagonal terms of O are formed by the taking square of uncertainties in the GR AAODs which are estimated as explained below.…”
mentioning
confidence: 85%
“…Due to this, the final assimilated AODs (for Chung et al (2005) and Adhikary et al (2008)) over most parts of Indian region are largely represented by satellite retrieved AODs with their inherent large uncertainties as discussed earlier. 5 More recently, Singh et al (2017) have combined AODs simulated by ECMWF with those retrieved by MODIS, Multiangle Imaging SpectroRadiometer (MISR) as well as in situ measured AODs by total 35 AERONET stations spread over Indian as well as Arabian region. However, even in this case employing about 17 AEORNET stations over Indian region, most of these stations were in the monsoon trough region and north-east India with no representation of other parts of the domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation